Educação e autonomia do município: o dito e o feito - Duarte, Elisa Aparecida Ferreira Guedes (2005)
This paper has got the objective of analyzing the autonomy process of the municipal regions concerning its educational policies in Brazil. The research took in account the phenomena of decentralization, deconcentration, municipalization and autonomy. In order to achieve this goal, a historical study about the outdated conceptions of the State and its evolvement in time was done, what clearly depicts, as an outcome, the updated notion of the State of Brazil and its municipal regions nowadays. Then, the range of the educational public policies was discussed in the remodelling scenary of the Contemporary State related to the distribution of functions and roles among the federate beings. In the quest of identifying a possible autonomy for these educational public policies, this study was focused on the district of Patos de Minas, Minas Gerais and its educational system during the period of 1997 to 2003. A bibliographical research about the development process of Brazil was done as a first step. Afterwards, the Brazilian Federal Constitution of 1988 was brought into context, especially in the articles related to education. The Fourteenth Amendment, the law that created a National Fund for Maintenance and Enrichment of the Educational System (FUNDEP Fundo Nacional de Manutencao e Valorizacao do Magistério) and the law of Aims and Bases for the National Education (Lei 9394/96 LDB Lei de Diretrizes e Bases da Educacao Nacional) were deeply studied in order to detect the real extension of the municipal autonomy. Also, other texts, laws, projects, reports, statements and statistic data form the district of Patos de Minas were analyzed. The decentralization related to the educational policies is indeed regulated by the Law of Aims and Bases for the National Education, the so called "LDB". This regulation is committed to a flexible educational policy, what allows the municipal regions to focus on its own, according to their profile. The deconcentration, though, engages the municipal regions to maintain the common schools only, without the responsibility to create their own teaching and methodology system, what means that the common schools belong to the States. The municipalization itself does not permit us to analyze its credits. It relies on the commitment of each county. Also, the autonomy is ruled and implies the capacity to develop the municipal educational system. However, this autonomy can be limited by the municipal budget, by its illegal or improper use, by the poverty of the assisted population and the economy itself. It came to the conclusion that, beyond all the law about the Educational System, maybe it is the public policies, among them the educational one, that creates a barrier to the evolvement of the districts. This fact demands a great self-government capacity to strengthen the municipal autonomy. The State of Brazil controls the educational policies through the "LDB" Law, systemic assessments, PNLD and PCNs. It is known, although, that there are municipal regions developing its proper autonomy.